Preparation method of nano WC-Co hard alloy for micro drilling

By using ultrafine cobalt oxide powder and cemented carbide grain growth inhibitors in the preparation process of PCB micro-drilling cemented carbide, the problem of drill needle fracture caused by cobalt lake or cobalt pond phenomenon is solved, achieving a more uniform material distribution and a higher service life.

CN119710345APending Publication Date: 2025-03-28ZHUZHOU XINKE HARD ALLOY
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202311264189.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

There is a cobalt lake or cobalt pond in the existing cemented carbide rods for PCB micro-drilling, which leads to the drilling needle being very prone to fracture in the cobalt lake part.

Method used

The preparation method of nano-WC-Co cemented carbide is adopted. By using ultrafine cobalt oxide powder instead of ultrafine cobalt powder, and adding cemented carbide grain growth inhibitors and molding agents to the alloy production process, the distribution of cobalt in the alloy is controlled through ball milling, drying, molding and removal of molding agents, and avoiding the formation of cobalt lakes or cobalt ponds.

Benefits of technology

The distribution of cobalt in the alloy is effectively controlled, the occurrence of cobalt lakes or cobalt ponds is reduced, the service life of drilling needles and the uniformity of materials are improved, and the production cost and energy consumption are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of alloy materials, and discloses a preparation method of a nano WC-Co hard alloy for micro drilling, the nano WC-Co hard alloy comprises the following raw materials by weight: 83-92 wt% of nano tungsten carbide, 7-17 wt% of ultrafine cobalt oxide powder, 0-1.5 wt% of a hard alloy grain growth inhibitor, and 0.2-3 wt% of a forming agent; the method comprises the following steps: 1, mixing nano tungsten carbide, superfine cobalt oxide powder, vanadium carbide and a forming agent, and adjusting a carbon balance point in the powder to be mixed by using free carbon black; 2, sequentially putting the powder and a forming agent into a ball mill, and mixing the materials by taking absolute ethyl alcohol as a ball milling medium; the superfine cobalt oxide powder is used for replacing superfine cobalt powder, so that the extension area of cobalt element powder is increased, the problem that the cobalt powder is extended into a sheet shape is avoided, the cobalt pool phenomenon is effectively reduced, meanwhile, crystal grain growth inhibition carbides are increased, the phenomenon that a binding phase in hard alloy is not uniform is avoided, the service life of the finished micro-small-diameter drill bit special for the PCB is guaranteed, and the service life of the finished micro-small-diameter drill bit special for the PCB is prolonged. And the product quality is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy materials, in particular to a method for preparing nano WC-Co hard alloy for micro-drilling. Background Art

[0002] With the development of electronic science and technology, the integration degree of PCB boards is getting higher and higher, which has led to an increasing demand for micro-diameter drills for processing PCB boards. Although my country is a major producer of PCB micro-drills, the production of cemented carbide rods for PCB micro-drills below 0.3 mm is basically dependent on imports. The main problems of domestically produced cemented carbide rods for PCB micro-drills are insufficient rigidity and bending strength of the alloy, and the internal structure of the alloy is uneven, resulting in the service life of the alloy drill not meeting the technical requirements of market use.

[0003] The existing cemented carbide rods for PCB micro-drilling use nano WC powder below 0.2μm in production and manufacturing, with ultrafine cobalt powder (0.8μm-1.2μm) or ultrafine nickel powder or a mixture of the two. In order to prevent the ultrafine powder from abnormally growing during the production and sintering process, the corresponding carbide is added as the grain growth inhibitor of the alloy in the first stage of the mixture preparation process of the alloy production. At the same time, ultrafine tungsten powder or free carbon black is added to the mixture according to the carbon content in the carbide, so that the uncombined carbon in the alloy after alloying reaches a balance point. Different powders are put into a ball mill according to the established formula and alcohol is added. After ball milling, drying, adding molding agent and mixing, the mixture is quenched. After extrusion molding-sintering and other processes, cemented carbide rod materials are obtained. In the existing alloy production process, the preparation of the ultrafine cobalt powder used is generally to reduce the ultrafine grain cobalt oxide at 400-500°C at a certain hydrogen flow rate using a slide rail tube furnace. In the process of reducing the cobalt oxide to metallic cobalt, the metal atoms between adjacent particles diffuse at high temperature to form a bonding surface, which eventually causes the metal particles to grow or produce branched sponge cobalt. The sponge cobalt is then crushed into ultrafine cobalt powder by a high-speed crusher. There is coarse dendritic cobalt powder in the crushed cobalt powder. Since cobalt has good ductility, the coarse dendritic cobalt powder cannot be eliminated during the ball milling process, and finally a cobalt lake or cobalt pool phenomenon is produced in the cemented carbide.

[0004] For PCB micro drills below 0.3mm, if a cobalt pool or a cobalt lake appears in the cemented carbide material, when the cobalt pool or the cobalt lake in the alloy is in the use part of the drill needle, the uneven wear of the material due to uneven materials in the use part of the drill needle and other factors can easily cause the drill needle to break in the cobalt lake part. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, which solves the problem of coarse dendritic cobalt powder in cobalt powder. Since cobalt has good ductility, the coarse dendritic cobalt powder cannot be eliminated during the ball milling process, and finally a cobalt lake or cobalt pool is generated in the cemented carbide, which causes the drill bit to easily break in the cobalt lake part.

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 83-92wt% of nano tungsten carbide, 7-17wt% of ultrafine cobalt oxide powder, 0-1.5wt% of cemented carbide grain growth inhibitor, and 0.2-3wt% of forming agent.

[0007] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0008] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, cemented carbide grain growth inhibitor and forming agent to form a mixed powder, and adjust the carbon balance point in the powder to be mixed with free carbon black;

[0009] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials;

[0010] Step 3, vacuum drying the ground mixed powder to obtain a mixed powder;

[0011] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0012] Step 5: Remove the forming agent from the blank in a hydrogen atmosphere at a certain flow rate of 200-550°C, and at the same time remove oxygen from the iron group metal oxides in the blank.

[0013] Preferably, in step 1, the grain size of the nano-tungsten carbide is less than 200 nm, and the particle size of the ultrafine cobalt oxide powder is less than 0.7 μm.

[0014] Preferably, in step 1, the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide.

[0015] Preferably, in step 1, the free carbon black is used to adjust the carbon balance of the mixed powder, and the carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%.

[0016] Preferably, in step 2, the rotation speed of the ball mill is 200-300 r / min, the grinding time of the ball mill is 2-5 h, and the ball mill uses grinding balls with a diameter of 5-7 mm.

[0017] Preferably, in step 2, the liquid-to-solid ratio of the anhydrous ethanol to the powder is 350-370 ml / kg.

[0018] Preferably, in step three, the vacuum drying temperature of the mixed powder is 90-95°C.

[0019] Preferably, in step five, the hydrogen atmosphere flow rate is 3-4.5 m3 / h.

[0020] The present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling. It has the following beneficial effects:

[0021] 1. The present invention adopts ultrafine cobalt oxide powder instead of ultrafine cobalt powder in the production process. Since the particle size uniformity and dispersibility of ultrafine cobalt oxide powder are better than those of ultrafine cobalt powder, and the ductility of cobalt oxide is poor, in the process of preparing cemented carbide mixture, a small amount of coarse particles of cobalt oxide powder are easily ground by grinding rods during ball milling, thereby avoiding the phenomenon that coarse cobalt powder is stretched into sheets, thereby effectively controlling the generation of cobalt lakes or cobalt pools in the alloy.

[0022] 2. The present invention not only reduces the energy consumption and production costs generated by reducing iron metal oxides with hydrogen alone, but also avoids the problem of the diffusion of metal atoms between adjacent particles at high temperatures to form bonding surfaces during the reduction of pure metal oxides, which ultimately causes the growth of metal particles, avoids the phenomenon of uneven bonding phase in cemented carbide, and further improves the quality of the product.

[0023] 3. The present invention adopts nano (200 nanometers) WC powder to realize the localization of imported products, and plays a positive role in promoting the research and development, production and quality control of domestic WC powder below 200 nanometers. DETAILED DESCRIPTION

[0024] The following will be combined with the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1:

[0026] The embodiment of the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 90wt% of nano tungsten carbide, 7wt% of ultrafine cobalt oxide powder, 0.75wt% of cemented carbide grain growth inhibitor, 2.25wt% of forming agent and free carbon black.

[0027] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0028] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and a forming agent to form a mixed powder, and use free carbon black to adjust the carbon balance point in the powder to be mixed. The grain size of nano tungsten carbide is less than 200nm, the particle size of ultrafine cobalt oxide powder is less than 0.7μm, and the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide. Free carbon black is used to adjust the carbon balance of the mixed powder. The carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%;

[0029] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials. The ball mill speed is 250r / min, the grinding time of the ball mill is 5h, the ball mill uses a grinding ball with a diameter of 5mm, and the liquid-solid ratio of anhydrous ethanol to powder is 350ml / kg;

[0030] Step 3: vacuum drying the ground mixed powder to obtain a mixed powder, and the vacuum drying temperature of the mixed powder is 92.5° C.;

[0031] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0032] Step 5: Remove the forming agent from the blank in a hydrogen atmosphere at a certain flow rate at 375°C, and at the same time remove the oxygen in the iron group metal oxides in the blank. The hydrogen atmosphere flow rate is 4.5m3 / h.

[0033] Embodiment 2:

[0034] The embodiment of the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 83wt% of nano tungsten carbide, 14wt% of ultrafine cobalt oxide powder, 0.75wt% of cemented carbide grain growth inhibitor, 2.25wt% of forming agent and free carbon black.

[0035] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0036] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and a forming agent to form a mixed powder, and use free carbon black to adjust the carbon balance point in the powder to be mixed. The grain size of nano tungsten carbide is less than 200nm, the particle size of ultrafine cobalt oxide powder is less than 0.7μm, and the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide. Free carbon black is used to adjust the carbon balance of the mixed powder. The carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%;

[0037] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials. The ball mill speed is 250r / min, the grinding time of the ball mill is 5h, the ball mill uses a grinding ball with a diameter of 5mm, and the liquid-solid ratio of anhydrous ethanol to powder is 350ml / kg;

[0038] Step 3: vacuum drying the ground mixed powder to obtain a mixed powder, and the vacuum drying temperature of the mixed powder is 92.5° C.;

[0039] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0040] Step 5: Remove the forming agent from the blank in a hydrogen atmosphere at a certain flow rate at 375°C, and at the same time remove the oxygen in the iron group metal oxides in the blank. The hydrogen atmosphere flow rate is 4.5m3 / h.

[0041] Embodiment three:

[0042] The embodiment of the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 87wt% of nano tungsten carbide, 10.75wt% of ultrafine cobalt oxide powder, 0wt% of cemented carbide grain growth inhibitor, 2.25% of forming agent and free carbon black.

[0043] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0044] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and a forming agent to form a mixed powder, and use free carbon black to adjust the carbon balance point in the powder to be mixed. The grain size of nano tungsten carbide is less than 200nm, the particle size of ultrafine cobalt oxide powder is less than 0.7μm, and the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide. Free carbon black is used to adjust the carbon balance of the mixed powder. The carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%;

[0045] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials. The ball mill speed is 250r / min, the grinding time of the ball mill is 5h, the ball mill uses a grinding ball with a diameter of 5mm, and the liquid-solid ratio of anhydrous ethanol to powder is 350ml / kg;

[0046] Step 3: vacuum drying the ground mixed powder to obtain a mixed powder, and the vacuum drying temperature of the mixed powder is 92.5° C.;

[0047] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0048] Step 5: Remove the forming agent from the blank in a hydrogen atmosphere at a certain flow rate at 375°C, and at the same time remove the oxygen in the iron group metal oxides in the blank. The hydrogen atmosphere flow rate is 4.5m3 / h.

[0049] Embodiment 4:

[0050] The embodiment of the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 87wt% of nano tungsten carbide, 10.75wt% of ultrafine cobalt oxide powder, 1.5wt% of cemented carbide grain growth inhibitor, 2.25wt% of forming agent and free carbon black.

[0051] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0052] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and a forming agent to form a mixed powder, and use free carbon black to adjust the carbon balance point in the powder to be mixed. The grain size of nano tungsten carbide is less than 200nm, the particle size of ultrafine cobalt oxide powder is less than 0.7μm, and the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide. Free carbon black is used to adjust the carbon balance of the mixed powder. The carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%;

[0053] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials. The ball mill speed is 250r / min, the grinding time of the ball mill is 5h, the ball mill uses a grinding ball with a diameter of 5mm, and the liquid-solid ratio of anhydrous ethanol to powder is 350ml / kg;

[0054] Step 3: vacuum drying the ground mixed powder to obtain a mixed powder, and the vacuum drying temperature of the mixed powder is 92.5° C.;

[0055] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0056] Step 5: Remove the forming agent from the blank in a hydrogen atmosphere at a certain flow rate at 375°C, and at the same time remove the oxygen in the iron group metal oxides in the blank. The hydrogen atmosphere flow rate is 4.5m3 / h.

[0057] Embodiment five:

[0058] The embodiment of the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 87wt% of tungsten carbide, 10.75wt% of ultrafine cobalt oxide powder, 0% of cemented carbide grain growth inhibitor, 2.25wt% of forming agent and free carbon black.

[0059] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0060] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and a forming agent to form a mixed powder, and use free carbon black to adjust the carbon balance point in the powder to be mixed. The grain size of nano tungsten carbide is less than 200nm, the particle size of ultrafine cobalt oxide powder is less than 0.7μm, and the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide. Free carbon black is used to adjust the carbon balance of the mixed powder. The carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%;

[0061] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials. The ball mill speed is 250r / min, the grinding time of the ball mill is 5h, the ball mill uses a grinding ball with a diameter of 5mm, and the liquid-solid ratio of anhydrous ethanol to powder is 350ml / kg;

[0062] Step 3: vacuum drying the ground mixed powder to obtain a mixed powder, and the vacuum drying temperature of the mixed powder is 92.5° C.;

[0063] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0064] Step 5: Remove the forming agent from the blank in a hydrogen atmosphere at a certain flow rate at 200°C, and at the same time remove the oxygen in the iron group metal oxides in the blank. The hydrogen atmosphere flow rate is 4.5m3 / h.

[0065] Embodiment six:

[0066] The embodiment of the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 87wt% of tungsten carbide, 10.75wt% of ultrafine cobalt oxide powder, 0% of cemented carbide grain growth inhibitor, 2.25wt% of forming agent and free carbon black.

[0067] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0068] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and a forming agent to form a mixed powder, and use free carbon black to adjust the carbon balance point in the powder to be mixed. The grain size of nano tungsten carbide is less than 200nm, the particle size of ultrafine cobalt oxide powder is less than 0.7μm, and the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide. Free carbon black is used to adjust the carbon balance of the mixed powder. The carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%;

[0069] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials. The ball mill speed is 250r / min, the grinding time of the ball mill is 5h, the ball mill uses a grinding ball with a diameter of 5mm, and the liquid-solid ratio of anhydrous ethanol to powder is 350ml / kg;

[0070] Step 3: vacuum drying the ground mixed powder to obtain a mixed powder, and the vacuum drying temperature of the mixed powder is 92.5° C.;

[0071] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0072] Step 5: Remove the forming agent from the blank in a hydrogen atmosphere at a certain flow rate of 550°C, and at the same time remove the oxygen in the iron group metal oxides in the blank. The hydrogen atmosphere flow rate is 4.5m3 / h.

[0073] Embodiment seven:

[0074] The embodiment of the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 90wt% of nano tungsten carbide, 7wt% of ultrafine cobalt oxide powder, 0.75wt% of cemented carbide grain growth inhibitor, 0.2wt% of molding agent and free carbon black.

[0075] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0076] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and a forming agent to form a mixed powder, and use free carbon black to adjust the carbon balance point in the powder to be mixed. The grain size of nano tungsten carbide is less than 200nm, the particle size of ultrafine cobalt oxide powder is less than 0.7μm, and the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide. Free carbon black is used to adjust the carbon balance of the mixed powder. The carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%;

[0077] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials. The ball mill speed is 250r / min, the grinding time of the ball mill is 5h, the ball mill uses a grinding ball with a diameter of 5mm, and the liquid-solid ratio of anhydrous ethanol to powder is 350ml / kg;

[0078] Step 3: vacuum drying the ground mixed powder to obtain a mixed powder, and the vacuum drying temperature of the mixed powder is 92.5° C.;

[0079] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0080] Step 5: Remove the forming agent from the blank under a certain flow of hydrogen atmosphere at 375℃, and remove the oxygen in the iron group metal oxides in the blank at the same time. The hydrogen atmosphere flow rate is 4.5m 3 / h.

[0081] Embodiment eight:

[0082] The embodiment of the present invention provides a method for preparing nano WC-Co cemented carbide for micro-drilling, comprising the following raw materials in weight percentage: 90wt% of nano tungsten carbide, 7wt% of ultrafine cobalt oxide powder, 0.75wt% of cemented carbide grain growth inhibitor, 3wt% of forming agent and free carbon black.

[0083] A method for preparing nano WC-Co cemented carbide for micro-drilling comprises the following steps:

[0084] Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and a forming agent to form a mixed powder, and use free carbon black to adjust the carbon balance point in the powder to be mixed. The grain size of nano tungsten carbide is less than 200nm, the particle size of ultrafine cobalt oxide powder is less than 0.7μm, and the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide. Free carbon black is used to adjust the carbon balance of the mixed powder. The carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%;

[0085] Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials. The ball mill speed is 250r / min, the grinding time of the ball mill is 5h, the ball mill uses a grinding ball with a diameter of 5mm, and the liquid-solid ratio of anhydrous ethanol to powder is 350ml / kg;

[0086] Step 3: vacuum drying the ground mixed powder to obtain a mixed powder, and the vacuum drying temperature of the mixed powder is 92.5° C.;

[0087] Step 4: passing the mixed material powder through a molding device to obtain a molding blank;

[0088] Step 5: Remove the forming agent from the blank under a certain flow of hydrogen atmosphere at 375℃, and remove the oxygen in the iron group metal oxides in the blank at the same time. The hydrogen atmosphere flow rate is 4.5m 3 / h.

[0089] Alloy quality test:

[0090] According to the above-mentioned examples 1 to 8, the mass percentages of nano-tungsten carbide, ultrafine cobalt oxide powder, vanadium carbide and forming agent in the mixture were adjusted respectively, and the hard alloy was prepared at different ball milling speeds and different reduction temperatures, and the obtained hard alloy was observed, as shown in the following table:

[0091]

[0092] Summary: Practice has proved that when ultrafine cobalt oxide powder is used, the occurrence rate of cobalt pool phenomenon decreases. When the tungsten content and the weight percentage of the forming agent increase, the tensile strength of the hardness alloy increases. When the cobalt content in the alloy increases, the hardness, wear resistance, chemical stability and thermal stability of the hardness alloy increase positively. Compounds such as vanadium carbide can effectively inhibit the growth of alloy grains. At the same time, when the cobalt content increases, the grain growth can also be inhibited. Iron oxides are reduced faster in a higher temperature environment.

[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nano WC-Co hard alloy for micro-drilling, characterized by: The raw materials include the following weight percentages: 83-92wt% of nano tungsten carbide, 7-17wt% of ultrafine cobalt oxide powder, 0-1.5wt% of cemented carbide grain growth inhibitor, and 0.2-3wt% of molding agent.

2. A method for preparing nano WC-Co cemented carbide for micro-drilling, characterized in that: The nano WC-Co hard alloy for micro-drilling as claimed in claim 1 comprises the following steps: Step 1: Mix nano tungsten carbide, ultrafine cobalt oxide powder, cemented carbide grain growth inhibitor and forming agent to form a mixed powder, and adjust the carbon balance point in the powder to be mixed with free carbon black; Step 2: sequentially put the above powder and forming agent into a ball mill, and use anhydrous ethanol as a ball milling medium to mix and grind the materials; Step 3, vacuum drying the ground mixed powder to obtain a mixed powder; Step 4: passing the mixed material powder through a molding device to obtain a molding blank; Step 5: Remove the forming agent from the blank in a hydrogen atmosphere at a certain flow rate of 200-550°C, and at the same time remove oxygen from the iron group metal oxides in the blank.

3. The method for preparing nano WC-Co cemented carbide for micro-drilling according to claim 2, characterized in that: In step 1, the grain size of the nano-tungsten carbide is less than 200 nm, and the grain size of the ultrafine cobalt oxide powder is less than 0.7 μm.

4. The method for preparing nano WC-Co cemented carbide for micro-drilling according to claim 2, characterized in that: In step 1, the cemented carbide grain growth inhibitor is one or more carbides such as vanadium carbide, chromium carbide, tantalum carbide, niobium carbide and molybdenum carbide.

5. The method for preparing nano WC-Co cemented carbide for micro-drilling according to claim 2, characterized in that: In step 1, the free carbon black is used to adjust the carbon balance of the mixed powder, and the carbon balance point is reached when the carbon content in the cemented carbide reaches 6.13wt%.

6. The method for preparing nano WC-Co cemented carbide for micro-drilling according to claim 2, characterized in that: In step 2, the rotation speed of the ball mill is 200-300 r / min, the grinding time of the ball mill is 2-5 h, and the ball mill uses grinding balls with a diameter of 5-7 mm.

7. The method for preparing nano WC-Co cemented carbide for micro-drilling according to claim 2, characterized in that: In step 2, the liquid-to-solid ratio of the anhydrous ethanol to the powder is 350-370 ml / kg.

8. The method for preparing nano WC-Co cemented carbide for micro-drilling according to claim 2, characterized in that: In step 3, the vacuum drying temperature of the mixed powder is 90-95°C.

9. The method for preparing nano WC-Co cemented carbide for micro-drilling according to claim 2, characterized in that: In step 5, the flow rate of the hydrogen atmosphere is 3-4.5 m3 / h.

Citation Information

Cited By

  • Hard alloy numerical control blade with excellent cutting performance and preparation method thereof

    CN122425207A

  • Ultra-coarse-grain high-toughness hard alloy and preparation method thereof

    CN122466290A

  • Super coarse grain high toughness cemented carbide and method for producing the same

    CN122466290B